Pengaruh E-LKPD Berbasis Inkuiri Terbimbing terhadap Keterampilan Proses Sains Peserta Didik Kelas VIII SMPN 8 Makassar - Huznul Amalia S; ramlawati ramlawati; Hasanuddin Hasanuddin (Universitas Negeri Makassar, 2023)
This study is a quasi-experiment research that aims to determine: (1) The level of science process skills of VIII grade students of SMPN 8 Makassar before and after the application of E-LKPD based on guided inquiry (2) The level of science process skills of VIII grade students of SMPN 8 Makassar before and after the application of printed LKPD based on guided inquiry (3) The improvement of science process skills of VIII grade students of SMPN 8 Makassar who are taught using E-LKPD based on guided inquiry (4). The effect of using E-LKPD based on guided inquiry on the science process skills of VIII grade students of SMPN 8 Makassar. This study used a research design of Nonequivalent Control Group Design. The sample consists of 2 classes, namely class VIII3 and VIII4 each totaling 37 people. The data were analyzed with descriptive statistics and inferential statistics. The results showed that: (1) The level of science process skills of VIII grade students of SMPN 8 Makassar before being applied was in the low category with a score of 7.38 and after being applied was in the medium category with a score of 16.97. (2) The level of science process skills of VIII grade students of SMPN 8 Makassar before being applied was in the low category with a score of 6.88 and after being applied was in the medium category with a score of 13.37. (3) The improvement of science process skills of VIII grade students of SMPN 8 Makassar who applied E-LKPD based on guided inquiry was in the medium category with N-Gain 0.54. (4) Based on the results of inferential analysis that tcount> ttable on science process skills, namely 9.57> 1.29 so that there is an effect of E-LKPD based on guided inquiry on the science process skills of class VIII students of SMPN 8 Makassar.